Pemberdayaan Kelompok Petani Jeruk Siam Menjadi Olahan Berbasis Pangan Fungsional Di Desa Brebeg Kecamatan Jeruk Legi Kabupaten Cilacap - Rachmawati, Indra; Indratmoko, Septiana; Puspo Aji, Ajeng; Tajudin, Tatang; Susanti , Susanti (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
Brebeg Village has great potential for producing Siamese oranges. Large areas of land have the productivity to produce more oranges, oranges can be harvested on average 18 tons per year. The large potential of orange fruit can improve the economy of orange farmers, the government Department of Agriculture provides assistance in the form of training on the care and rejuvenation of orange trees as well as providing training on processing orange fruit products in collaboration with UNAIC. The problems faced by Gapoktan are a lack of knowledge regarding planting oranges, an irregular irrigation system. The problems faced by KWT are lack of knowledge regarding orange-based products, product management and marketing. The method used is coordinating with all partners, providing knowledge and skills in creating orange cultivation facilities and orange-based food processing, implementing and evaluating activities. The results of Kosabangsa's research are able to provide benefits for community empowerment in this case, namely improving the economy through empowering Siamese orange farmer groups to become functional food-based processed products in Brebeg Village, Jeruklegi District, Cilacap Regency.